Gaps in maternal-fetal interface rejection response: chronic histiocytic intervillositis - Zhang, Xiaoqian; Fang, Zhenya; Wang, Xietong (Frontiers in Immunology, 2025)
Chronic Histiocytic Intervillositis (CHI) is a severe placental inflammatory response caused by various atypical antigens, attracting attention due to its high recurrence rate, which results in adverse pregnancy outcomes such as miscarriage and fetal growth restriction. The pathogenesis of CHI is still poorly understood. Immune factors such as autoimmune diseases or viral infections, maternal-fetal genetic compatibility, and other factors cause immune imbalance at the maternal-fetal interface. Disorders of immune tolerance in CHI includes abnormal activity of Cytotrophoblasts, mononuclear macrophages, and CD8+/CD4+ T lymphocytes. Additionally, pro-inflammatory factors such as IL-1β, TNF-α, and anti-inflammatory molecules like IL-10, TGF-β, and fibrin are crucial in regulating the pathological formation of CHI. Histopathological sections and staining, serological screening, and medical imaging techniques are the primary methods for diagnosing CHI. Patients with CHI may benefit from treatments including immunosuppressants, anticoagulants, and monoclonal antibodies.